Understanding and addressing adult sexual attraction to children: a study of paedophiles in contemporary society - Goode, Sarah D. (Routledge, 2010)
Understanding paedophiles -- Paedophiles online -- Setting up the "minor attracted adults" daily lives project -- Running the "minor attracted adults" daily lives project -- Findings from the minor-attracted adults daily lives research -- Constructing and negotiating identities -- Attraction and fantasies -- Experiences of support -- Debate and dissent within the online paedophile community -- What stops adults preventing the abuse of children? -- Addressing adult sexual attraction to children